Multiharmonic Balance Analysis of a Jointed Friction Oscillator - Süß, Dominik; Willner, Kai (Proceedings of the ECCOMAS, 2012)
This paper deals with the investigation of a jointed structure in the frequency domain. Because of the nonlinearity of most jointed systems an usual approach doing this is the usage of the Harmonic Balance Method (HBM), assuming that a harmonic excitation of the system is leading to a harmonic response. But for systems where the steady state response is not harmonic but periodic or systems which might be excited periodically, this assumption does no longer obtain satisfying results. So an advanced approach has to be used and the single-harmonic ansatz of the HBM to describe the response displacements of the system is extended to multiple harmonic parts. This leads to the so called Multi Harmonic Balance Method (MHBM) which represents a Fourier-type approximation of the periodic quantities of a system. The MHBM is presented for a friction oscillator containing a bolted joint. Furthermore the method is utilized for a parameter identification in the frequency domain using FRF measurements.
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-TM.multih_1
Keywords: Harmonic balance; Jointed structures; Structural dynamics